The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1365-2702.2008.02425.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting pressure ulcer risk: a multifactorial approach to assess risk factors in a large university hospital population

Abstract: The derived risk assessment scale is an easy-to-understand, easy-to-use tool with good prognostic validity and can assist in effective application of preventive measures against pressure ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 17 publications
3
35
1
2
Order By: Relevance
“…This finding is consistent with research that demonstrated the relationship between age and the development of PU (19)(20)(21) . In contrast, a study of the theme indicates that despite the elderly having a known susceptibility for the development of PU, the proper thing is not to evaluate this variable in an isolated manner (22) .…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with research that demonstrated the relationship between age and the development of PU (19)(20)(21) . In contrast, a study of the theme indicates that despite the elderly having a known susceptibility for the development of PU, the proper thing is not to evaluate this variable in an isolated manner (22) .…”
Section: Discussionsupporting
confidence: 92%
“…2,7,8,[11][12][13][14][15][16][17][18][19] Four studies focused specifically on cardiac surgery patients, but the majority included cardiac surgery patients within a heterogeneous population of acute or critical care patients. A summative list of risk factors was compiled based on the findings from each of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Also important, data of 34,238 hospital patients showed that patients with insufficient nutrition were 61% more likely to develop a pressure ulcer than those patients who did not have nutritional insufficiency. Evidently, correction of the serum albumin levels constitutes a key factor in pressure ulcers prevention and treatment (23, 24). …”
Section: Discussionmentioning
confidence: 99%